A Common Active Intermediate in the Oxidation of Alkenes, Alcohols and Alkanes with H2O2 and a Mn(II)/Pyridin‐2‐Carboxylato Catalyst. Issue 1 (1st December 2022) - Kasper, Johann B.; Saisaha, Pattama; de Roo, Maurits; Groen, Mitchell J.; Vicens, Laia; Borrell, Margarida; de Boer, Johannes W.; Hage, Ronald; Costas, Miquel; Browne, Wesley R.
Abstract: The mechanism and the reactive species involved in the oxidation of alkenes, and alcohols with H2 O2, catalysed by an in situ prepared mixture of a Mn II salt, pyridine‐2‐carboxylic acid and a ketone is elucidated using substrate competition experiments, kinetic isotope effect (KIE) measurements, and atom tracking with 18 O labelling. The data indicate that a single reactive species engages in the oxidation of both alkenes and alcohols. The primary KIE in the oxidation of benzyl alcohols is ca. 3.5 and shows the reactive species to be selective despite a zero order dependence on substrate concentration, and the high turnover frequencies (up to 30 s −1 ) observed. Selective 18 O labelling identifies the origin of the oxygen atoms transferred to the substrate during oxidation, and is consistent with a highly reactive, e. g ., [Mn V (O)(OH)] or [Mn V (O)2 ], species rather than an alkylperoxy or hydroperoxy species. Abstract : Manganese oxidation chemistry : In line solution and head space Raman spectroscopy combined with 18 O atom tracking reveal a common reactive species in the manganese‐pyridine carboxylic acid catalysed oxidation of alkenes, alkanes and alcohols and unexpected disproportionation of H2 O2 .